ChemInform Abstract: Asymmetric Copper‐Catalyzed C—N Cross‐Couplings Induced by Visible Light. Issue 29 (June 2016) - Kainz, Quirin M.; Matier, Carson D.; Bartoszewicz, Agnieszka; Zultanski, Susan L.; Peters, Jonas C.; Fu, Gregory C.
Abstract: Fully substituted stereocenters are highly enantioselectively generated by photoinduced copper‐catalyzed coupling of readily available racemic tertiary alkyl chloride electrophiles with various amines.